INFLUENCE OF PROLONGED TRIPTERELIN-INDUCED CENTRAL DEPRIVATION OF TESTOSTERONE SYNTHESIS ON MORPHOLOGICAL STRUCTURE OF RAT’S LIVER - Polyvyana, O.A.; Shepitko, K.V.; Stetsuk, Ye.V.; Akimov, O.Ye.; Dubinin, D.S. (World of Medicine and Biology, 2020)
In recent years, the incidence of prostate cancer has increased worldwide. For example, in 2012, the GLOBOCAN project found that prostate cancer was the second most commonly diagnosed cancer and the fifth leading cause of cancer deaths among men worldwide. Insufficient testosterone can exacerbate liver damage caused by obesity. The aim of our study was to identify morphological changes in the liver of rats at the tissue and cellular levels, to study the processes of formation of reactive oxygen species and the intensity of lipid peroxidation during prolonged central deprivation of testosterone synthesis caused by triptereline. Triptorelin-induced central deprivation of testosterone synthesis leads to oxidative damage to hepatocytes due to increased production of reactive oxygen species and decreased activity of antioxidant enzymes. Oxidative damage to liver cells begins at the molecular and cellular levels and becomes apparent at the tissue level on day 180 of the central deprivation of testosterone synthesis.